Autotoxicity of water extracts from different organs of potato - WAN Nianxin; YUAN Jichao; HE Wei; LONG Wenjing; ZHANG Qin; ZHOU Shaomeng; ZHENG Shunlin (浙江大学学报. 农业与生命科学版, 2016)
Continuous cropping obstacle caused by intensive cropping of potato has seriously affected its healthy development of industrialization. Autotoxicity was confirmed to be one of the mechanisms causing continuous cropping obstacle; therefore it will be significance to study the autotoxicity of potato for sustainable agriculture production. The growth of plants can be inhibited by autotoxicity through regulating the permeability of cell membrane, affecting the function and enzymatic activities, and even the photosynthesis system. It was so difficult to eliminate the continuous cropping obstacle by agronomic measures, thus it become necessary to solve the problem of continuous cropping obstacle and to reveal the mechanism of autotoxicity for potato.In this paper, a pot experiment was conducted to investigate effects of water extracts from different organs (root, stem and leaf) of potato on its growth and development. The potatoes were collected from tuber of mature potato in the field, and matrix culture method was adopted to conduct the experiments. Morphological characteristics of root system (root length, root surface area and root volume), and physiological parameters (catalase, peroxidase and malondiadehyde) were used as indicators to study the autotoxicity effect.The results showed that: Water extracts from different organs of potato exhibited obvious inhibitory effect on the growth of potato, and the extracts from stem and leaves had significant inhibitory effect on the height of potato (P<0.05), with the alleopathic response index (RI) value of -0.11. The root extracts significantly inhibited the number of branches and stem diameter, with the RI value of -0.11 and -0.13, respectively. Meanwhile, the damage of root system caused by the root extracts was also worst, with the RI value of -0.25 for the root surface area, -0.32 for the root tip number, and -0.32 for the branch number, respectively. The chlorophyll contents of potato leaf, activities of peroxidase and catalase all decreased under the treatments of water extracts from different organs of potato; however, the MDA content was increased, and the allelopathic effect of root extracts was the strongest, with the RI value of -0.10. The soluble sugar content was significantly increased by the root extracts, while reduced by the stem and leaf extracts, with the RI value of -0.11 and -0.02, respectively. On the contrary, the soluble protein content was increased by the stem and leaf extracts, while reduced by the root extracts, with the RI value of -0.06.In conclusion, the autotoxicity effect is observed in different organs of potato, but the adaptation to allelochemicals is distinct among the different organs of potato, and the inhibitory effect by root extracts is strongest.